An Urban Project in Rural Crisis: Responding to Coronavirus in Bulgarian Villages - Craycraft, Sarah (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2021)
The unprecedented situation of COVID-19 has created a unique response from village-based projects in rural Bulgaria. My research from 2019-2020 followed three projects that facilitate urban-rural intergenerational connection as a form of rural reinvestment. With project planning uncertain and interactions between generations discouraged due to the pandemic, my research, and the cultural work I am following, took an unexpected turn. Rather than fulfilling their core missions of connecting young and old, rural and urban people together to pass on rural culture, these projects transformed their rhetoric and practices to support the elderly in a time of crisis. By drawing on my experiences in the field throughout Bulgaria’s early onset of pandemic and lockdown measures as well as “virtual ethnography” (being in the virtual spaces where communication and online events are happening), I explore how two of the intergenerational projects aimed at heritage-based rural reinvestment in Bulgaria have adapted and organized to fill different needs in a time of crisis. During the coronavirus pandemic, these projects served as a well-poised mechanism for responding quickly to shifting needs and contexts.